Model Efisiensi Arus pada Elektrolisis Serbuk Tembaga Menggunakan Metode Perancangan Percobaan Faktorial Desain 2K - Gunawan, R. Mohamad Fajar; Soleh Wahyudi; Andrie Harmaji; Diana Kamaliyah Ichsan; Gigih Safardwiyansyah; Naufal Dhiya Ulhaq (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2024)
This paper presents the results of developing a current efficiency model for copper powder electrolysis and analyzes the factors that most influence current efficiency using a 2K factorial experimental design. The three independent variables are copper ion (Cu) concentration, current density, and electrolysis time. Copper powder electrolysis experiments were conducted using a pure copper plate anode (99.88% Cu) and a 316L stainless steel cathode. Current efficiency is calculated based on data on the weight of the copper powder produced. Copper powder characterization uses a Scanning Electron Microscope (SEM) to determine the morphology and size distribution of the powder, X-ray Diffraction (XRD) to identify powder phases/compounds, Energy Dispersive X-ray Spectroscopy (EDX) to analyze the elemental composition and Particle Size Analyzer ( PSA) to determine the powder particle size and distribution. The prediction model obtains the highest current efficiency at 96%. The resulting copper powder has a dendritic structure morphology with an average particle size of 114.9 µm. It comprises cuprite (Cu2O) and copper (Cu) with a composition of 88.17% Cu and 11.83% O.